"Nosotras no Empezamos a Hacer Eso": A Social Semiotic View of a Sheltered Science Investigation. Issue 2 (21st October 2019) - Britsch, Susan
Abstract : This article traces the interaction of multimodal semiotic resources within and across tasks constituting a science unit on surface tension in an eighth‐grade sheltered science classroom. Two discourses, operating simultaneously, realized differently motivated signs. This article follows the contribution of linguistic and extralinguistic modes that impinged on science and language learning. These semiotic resources differently engaged the identities of the teacher and the focal English learning students. The teacher discourse cued students to read the available modes in a way that awarded them a behavioral identity in the classroom, but not a conceptual one. The English learners recognized and cooperated with the initial focus on behavioral compliance imposed by the teacher discourse while asserting peer identity, but late in the unit the teacher discourse shifted frames to require student enactment of conceptual identity through written language. The teacher discourse foregrounded, or was consistently undergirded by, the conceptual identity that the teacher brought to the classroom and by a set of expectations for a learning trajectory that did not explicitly link key language with students' investigative activity. In five of six task‐based interactions, the student discourse foregrounded behavioral or peer identity. As a result, the students were able to only partially link their science activity to the concept of surface tension using the language of science. Abstract :